The Functions and Impact of Fiscal Councils. (Policy Papers; Policy Paper ;, 2013)
In recent years, a rapidly growing number of countries have established independent agencies aimed at promoting sound fiscal policies. Although these institutions vary greatly in terms of their remit, tasks, and institutional forms, they tend to share an explicit mandate enshrined in legislation, a 'watchdog' role implying a direct contribution to the public debate on fiscal policy, and strict non-partisanship in their activities. Importantly, fiscal councils do not have the discretion to set policy instruments. Unlike independent central banks in the monetary policy area, they are only facilitators of sound fiscal public finances, not decision makers deliberately insulated from politics. Earlier IMF staff analysis of non-partisan fiscal agencies (IMF, 2005, expanded by Debrun, Hauner and Kumar, 2009) referred to the generic term of 'fiscal council' to designate these institutions. A handful of similar bodies have been in place for a long time-mostly in advanced economies.